Tinjauan Yuridis Atas Perlindungan Hukum Terhadap Fenomena Pembajakan Film Berdasarkan Undang-Undang No 28 Tahun 2014 Tentang Hak Kekayaan Intelektual - Ramadhan, Bayu Rahman; Apriani, Rani (Peneliti.net, 2025)
The phenomenon of film piracy is a detrimental thing, especially for film arts activists, where piracy is an act that is detrimental both materialistically and to their creations. In order to protect the rights of art, intellectual property rights are also being read, which also reads Law No. 28 of 2014 concerning Intellectual Property Rights, this paper will discuss how the effectiveness of the use of the UU Hakijakaan against the phenomenon of filmmakers, writing using normative juridical methods.